Physicochemical and Organoleptic Analysis of Tempeh Nuggets with Moringa Leaf Flour Formulation (Moringa oleifera): ANALISIS FISIKOKIMIA DAN ORGANOLEPTIK NUGGET TEMPEDENGAN FORMULASI TEPUNG DAUN KELOR (Moringa oleifera) - Nurhikma Uday; Tahir, Muh; Marleni Limonu (ROCE : Jurnal Pertanian Terapan, 2024)
Improving the nutritional quality of tempeh nuggets can be done through food processing with the addition of moringa leaf flour. This study aims to improve the nutrition of tempeh nugget products and determine the organoleptic properties of tempeh nuggets after adding moringa leaf flour. This study used a single-factor complete randomized design (RAL) (Moringa leaf flour formulation for tempeh nuggets) and 5 treatments; control (0 g moringa leaf flour), 1 g moringa leaf flour, 2 g moringa leaf flour, 3 g moringa leaf flour, 4 g moringa leaf flour. Each treatment was repeated 3 times. The results showed that the best treatment for making tempeh nuggets was obtained in the formulation of tempeh 50 g and moringa leaf flour 4 g on nutritional value. The value of protein is 9.37%, fat 12.73%, ash 2.17%, calcium 2.91%, and elasticity test 889.7g/f.